Optimizing Blood Sugar Control in Diabetes Mellitus: The Impact of Family Interventions :A Literature Review - Indra Junsen Asri; M Abu; Deliaty Bagenda Ali; Jenita Laurensia Saranga (PT.Mantaya Idea Batara, 2025)
Background: Diabetes Mellitus (DM) is a chronic disease that requires longterm management including optimal blood sugar control. Family support plays an important role in the successful management of diabetes by facilitating interventions that can improve adherence to healthy lifestyles and medical therapies. Objective: This study aimed to identify and analyze the role of family interventions blood glucose control in individuals with Diabetes Mellitus (DM). Design: A Literature Review was conducted. Data Sources: A systematic search ascross eight databases PubMed, ProQuest, Clinical Key Nursing, Science Direct, Cochrane, EBSCOhost, Wiley, and Gray Literature. Methods: The reviewed articles published between 2014 and 2019, examined the effects of family interventions on glycemic control and met the inclusion criteria. Articles addressing the role of family support in managing blood glucose levels in individuals with DM were included and critically appraised using the CASP tool. Results: Seven studies meeting the inclusion criteria were included in this review. The intervention type examined was the role of family interventions in individuals with DM. The literature review indicated a positive effect on glycemic control in individuals with DM following Family Intervention. Conclusions: This review included seven studies, all of which provided statistically significant results, and concluded that Family Intervention influences glycemic control in individuals with DM.